The Role of Primary Motor Cortex as a Marker for and Modulator of Pain Control and Emotional-Affective Processing - Felipe Fregni (Frontiers Research Topics, 2017)
The sensory and motor cortical homunculi proposed by Walter Penfield were a major landmark for the anatomical mapping of the brain. More than 60 years after, the development of new tools to investigate brain function non-invasively has increased our knowledge about the structure and functions of the primary motor Cortex (M1) beyond motor control in both humans and animals. This book highlights the role of the motor cortex that goes way beyond motor functioning. We were interested in both theoretical and empirical contributions related to electrophysiological, pharmacological, neuroimaging, and neuromodulatory studies exploring the role of M1 on non-motor functions, such as pain, abnormal neuroplasticity that may lead to chronic pain conditions; or the relationship between M1 and mental imagery or emotion. This book is comprised of 15 articles published in this edited volume as a research topic collection in Frontiers in Human Neuroscience titled "The Role of Primary Motor Cortex as a Marker and Modulator of Pain Control and Emotional-Affective Processing."